Fluoride Intake and Prevalence of Dental Fluorosis: - Samuel J. Fomon, MD; Jan Ekstrand, DDS, PhD; Ekhard E. Ziegler, MD (Blackwell Synergy, 2000)
Although the predominant beneficial effect of fluoride occurs locally in the mouth, the adverse effect, dental fluorosis, occurs by the systemic route. The caries attack rate in industrializedcountries, including the Unitedstates and Canada, has decreased dramatically over the past 40 years. However, the prevalence of dental fluorosis in the United States has increased during the last 30 years both in communities with fluoridated water and in communities with nonfluoridated water. Dental fluorosis is closely associated with fluoride intake during the period of tooth development